Optimization of some technological factors to soybean crop - Felicia Cheţan; Cornel Cheţan; Florin Russu; Alina Şimon; Adina Tărău; Adrian Ceclan; Marius Bărdaş (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
The research conducted at the Agricultural Research and Development Station Turda (ARDS), situated in the Transilvanian Plateau, they pursued the possibility of obtaining yield increases and quality for the Caro TD soybean variety, cultivated in four tillage systems (CS - conventional plow, MTC - minimum till chisel, MTD - minimum till disk, NT - no till direct sowing), by creating a larger space for plant nutrition and development. Sowing was done at 65 (germinative grains) gg/m2 , the distance between the rows being 18-36-54 cm. From the results obtained, in two experimental years, it was concluded that, in the climate and soil conditions of Turda, the tillage system corresponds to a certain sowing distance at which soybean lends itself, achieving higher yields: classic at 18 cm (3189 kg/ha), minimum till chisel at 36 cm (2779 kg/ha), minimum till disc at 54 cm (2875 kg/ha) and for no till direct sowing 36 cm (2349 kg/ha). It noted, the high percentage of protein content in the grains in the variant MTD (32,0% at 54 cm and 31,9% la 18 cm). The lowest values were recorded in the variant NT, at the same distances between the rows. The fact that in the variant NT the lowest values of grain protein content were determined, 30% at18 cm, respectively 29,6% at 54 cm distance between rows, and the highest percentage was found at the same distances between rows in the variant MTD, at 54 cm 32,0%, respectively at 18 cm 31,9%. In terms of fat content, the minimum range was 20% in SC at 18 cm and maximum in MTC at 36 cm distance between rows.
Keywords: Q01; Q15; Q16; 330; non-conventional system; distance between rows; yield; soybean